Formação, transformação e expansão dos quintais agroflorestais de agricultores familiares da Cooperativa D’Irituia, Pará - SILVA, Sinara Dias (Universidade Federal do Pará, 2022)
The various problems caused by the cutting and burning process demonstrate how important the soil is for the family farmer, so the use of management practices that enable nutrient cycling through the maintenance of organic matter and soil micro-life are essential. Therefore, this research aims to analyze the process of formation, transformation and expansion of agroforestry yards in family farmers production systems of Cooperative D'Irituia, Pará. To meet this proposal, it was decided to use a methodology based on the theoretical bases of the systemic approach. For this, 23 families of family farmers from the D'Irituia cooperative who have agroforestry yards and five key informants from the main institutions linked to rural dynamics were selected. of the municipality. The methodological tools adopted consisted of historical interviews, secondary data, semi-structured questionnaires, typology and chronicles of the establishments. The results showed the external factors that influenced the formation of agroforestry yards were the credit public policies such as FNO and Proambiente; the Secretary of Agriculture of Irituia and the cooperative D'Irituia itself. The agroforestry yards found in Irituia have a great diversity of species, including fruit and annuals. It is noteworthy that in 74% of the areas where agroforestry yards are currently installed were capoeira areas and 13% in fields. Through the typology it was possible to form two large groups, besides one of the main factors responsible for the transformation and expansion of agroforestry yards is the need to increase production. With the chronicles of the establishments we can observe that the events identified over time was not always the motivating factor of the changes identified within the agricultural establishments, however, it affected the two groups represented here, but differently. Therefore, it can be concluded that the agroforestry systems found today in the municipality of Irituia are of great importance in guaranteeing food sovereignty as well as in the socioeconomic development of these families, besides having an important role in environmental preservation.